Honduras - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
The Debt Sustainability Analysis (DSA) indicates that Honduras stands at low risk of debt distress both for public external debt and overall debt, which represents an upgrade from the 2018 DSA, where risk of debt distress was assessed as moderate. The DSA was undertaken under the revised debt-sustainability framework for low income countries (LIC DSF), whereby Honduras’s debt carrying capacity was upgraded from medium to strong. Changes in the debt-sustainability framework have contributed to the risk of debt distress improvement. A proven record of compliance with the Fiscal Responsibility Law (FRL) and solid macroeconomic conditions also contributed to rate Honduras’ risk of debt distress as low. Going forward, adherence to the FRL and institutional reforms to boost inclusive growth and increase the economy’s potential are critical to maintain debt sustainability.